MiR-760 overexpression promotes proliferation in ovarian cancer by downregulation of PHLPP2 expression - Liao, Yanbin; Deng, Yalan; Liu, Jun; Ye, Zhanying; You, Zeshan; Yao, Shuzhong; He, Shanyang (Gynecologic oncology, 2016)
Ovarian cancer is one of the most lethal gynecologic malignancies worldwide and with poor prognosis and survival rate in women. Identifying sensitive and specific molecular in carcinogenesis may improve diagnostic and therapeutic strategies for this malignancy and achieve a better clinical outcome. miR-760 expression in ovarian cancer cell lines and patient tissues were determined using Real-time PCR. 145 human ovarian cancer tissue samples were analyzed by RT-PCR to investigate the association between miR-760expression and the clinicopathological characteristics of ovarian cancer patients. Functional assays, such as MTT, anchorage-independent growth, colony formation and BRDU assay were used to determine the oncogenic role of miR-760 in human ovarian cancer progression. Furthermore, western blotting and luciferase assay were used to determine the mechanism of miR-760 promotes proliferation in ovarian cancer cells. The expression of miR-760 was markedly upregulated in ovarian cancer cell lines and tissues, and high miR-760 expression was associated with an aggressive phenotype and poor prognosis with ovarian cancer patients. Upregulation of miR-760 promoted, whereas downregulation of miR-760 inhibited the proliferation of ovarian cancer cells in vitro. Additionally, we identified PHLPP2 as a direct target of miR-760, and silencing the expression of PHLPP2 is the essential biological function of miR-760 during ovarian cancer cell proliferation. Finally, we showed a significant correlation between miR-760 and PHLPP2 expression in ovarian cancer tissues. Our findings suggest that miR-760 represents a potential onco-miR and participates in ovarian cancer carcinogenesis, which highlight its potential as a target for ovarian cancer therapy. •MiR-760 was significantly upregulated in ovarian cancer.•Overexpressing miR-760 promoted aggressiveness of ovarian cancer.•MiR-760 promoted ovarian cancer aggressiveness by suppressing PGLPP2 expression.